A randomized controlled trial of the effect of a nature-based intervention on climate capability and eco-anxiety in teenagers - Glynn, Róise; Dwyer, Clodagh O.; Casey, Monica; Sharma, Santosh; Harrold, Pat; O’Connor, Pat; Harrold, Patrick; Glynn, Liam G. (Frontiers in Psychology, 2025)
IntroductionWe are experiencing a climate and biodiversity crisis unprecedented in the history of mankind. Climate Capability is the degree to which individuals have the skills, understanding, and motivation to make behavioral changes that will reduce their individual contribution to climate change; and appreciate the need for collective action and governance to limit the magnitude of climate change and mitigate its effects. This novel randomized controlled trial tested an intervention to change climate capability in teenagers.MethodsThe study design was a randomized controlled trial recruiting teenagers from a single school community in Ireland. At baseline, prior to allocation, climate capability was measured using the climate capability scale in all participants. The intervention consisted of weekly online climate education and motivation messages and a supervised field trip. The primary outcome was change in climate capability score between baseline and follow-up.ResultsA total of 116 students were invited to participate and 86 (73%) agreed to do so and completed baseline data (Intervention = 43; Control = 43); 83 provided outcome data (Intervention = 43; Control = 40). There was evidence of a significant intervention effect (p < 0.01); with an increase in mean climate capability score of 8.2 (4.9–11.5) and an associated increase in eco-anxiety score of 7.2 (3.7–10.7) favoring the intervention. There was a statistically significant correlation between change in climate capability and change in eco-anxiety (Pearson correlation = 0.485, p < 0.001).DiscussionThe study results appear to confirm the effectiveness of a nature-based intervention in teenagers to build positive relationships with the environment and build their own capacity and capability to effect positive environmental change. Those responsible for developing school curricula should consider including climate education and engagement in the education of young people if we are to ensure that we have enough climate capable citizens of the future. The trial was registered with ISRCTN on 26/10/24 (No: 46298/www.isrctn.com/ISRCTN18655072).